Carbonic Anhydrase IX Enzyme in Triple Negative Breast Carcinoma: Relationship With Prognostic Factors and Response to Neoadjuvant Chemotherapy - Özgen Arslan Solmaz; Nizamettin Kutluer; Mehmet Buğra Bozan (European Journal of Breast Health)
Objective: Triple negative breast carcinoma (TNBC) is characterized by the absence of estrogen receptor, progesterone receptor and human epidermal growth factor receptor-2 receptor expression. Carbonic anhydrase IX (CA IX) is a tumor-associated cell surface glycoprotein that is involved in adaptation to hypoxia-induced acidosis and plays a role in cancer progression. The aim of this study was to investigate CA IX expression in TNBC and its relationship with treatment effect. Materials and Methods: Immunohistochemical staining was performed on tru-cut biopsy materials with CA IX antibody. Positive staining was graded as low (<10%) and high (>10%). In addition, the relationship between tumor diameter, histological grade and the treatment effect on mastectomy materials performed after neoadjuvant treatment was evaluated. Results: TNBCs with positive staining for CA IX exhibited higher histological grade, and higher Ki-67 index compared to TNBCs with negative staining (p < 0.05). The response to treatment decreased as the degree of CA IX staining increased. There was no significant difference between the high staining group and low staining group in terms of patient age, tumor diameter and breast localisation. Conclusion: CA IX enzyme is a poor prognostic marker in TNBC cases. However, overexpression of CA IX was associated with reduced response to treatment.